Thomas Becon's Henrician Writings: Composition and County Patronage, 1541–1543. Issue 1 (2nd January 2016) - Reimer, Jonathan
Abstract : This article explains seemingly discordant religious content found in the Henrician writings of Thomas Becon (c. 1512–1567) by reconstructing the social context in which these texts were written during the early 1540s. It shows that Sir Thomas Neville of Mereworth (c. 1482–1542), the Kentish patron to whom Becon dedicated the dialogues A Christmas Bankette and A Potacion for Lent, exercised considerable influence over the works that were addressed to him. In so doing, it highlights the capacity of literary patrons to be contributors to rather than merely consumers of mid-Tudor literature.